Environmental Contribution to the Effectiveness of Food Security Policy Implementation as A Rehabilitation Effort for Stunting Treatment in Rokan Hilir Regency - Yuliani Febri; Sulistyani Andri; Yusrizal Firdaus (E3S Web of Conferences)
According to SDGs 2030, food security must have 3 principles, namely; Availability, Affordability; and Benefits, hereinafter referred to as food security aspects. Rokan Hilir is an area with a high level of stunting. Referring to the problem formulation, the objectives of this research are: 1) to analyze and describe the effectiveness of the implementation of the Food Security Policy; 2) to analyze and describe the factors which constrain the effectiveness implementation the Food Security Policy in Rehabilitation Efforts to Handle Stunting in Rokan Hilir. A qualitative approach is taken by using descriptive analysis methods. Informants are including people and parties who are dealing to the food security policy innovations in handling stunting including local government staff, the community and non-government organization (NGOs). The research results show that stunting in children will have an impact on metabolic disorders, low immunity, and suboptimal physical body size. A good coordination and communication among the parties is a key of success to prevent higher cases and develop community awareness of stunting.